Gamma Hydroxybutyric Acid (GHB) for the Treatment of Alcohol Dependence: A Review - Caputo, Fabio; Vignoli, Teo; Maremmani, Icro; Bernardi, Mauro; Zoli, Giorgio (International journal of environmental research and public health, 2009)
Gamma-hydroxybutyric acid (GHB) is a short-chain fatty acid structurally similar to the inhibitory neurotransmitter γ-aminobutyric acid. Clinical trials have demonstrated that 50-100 mg/kg of GHB fractioned into three or six daily doses is able to suppress alcohol withdrawal symptoms and facilitates the maintenance of abstinence from alcohol. These studies have also shown that GHB craving episodes are a very limited phenomenon (about 10-15%). Thus, physicians with access should consider the clinical efficacy of GHB as a valid pharmacological tool for the treatment of alcohol addiction.